Study on seed germination and seedling growth models of sandalwood (Santalum album L.) of several mother seed trees in Belu Regency, East NusaTenggara - ALBERTUS HUSEIN WAWO (Society for Indonesian Biodiversity, 2008)
Sandalwood (Santalum album L.) is one of the economic plants that are threatened rare. Belu regency is a part of East Nusa Tenggara Province was known as center of natural distribution of sandalwood. In 2005 was found some mother seed trees at several locations in Belu are Suriklulik, Lelowae, Biau, Uabau, Haitimuk, Alas and Tialai. For research propose every location was chosen only one mother seed tree that was marked with capital letters as followed ; A is mother seed tree from Suriklulik, B from Lelowae, C from Biau, D from Uabau, E from Haitimuk, F from Alas and G from Tialai, In this research was studied the germination of sandalwood seeds from severalmother seed trees was mentioned above and some aspects of seedling growth include model of seedling growth and correlation between height and number of leaves growth during 5 months. This research was carried out in paranet house during 5 months and seedling was planted in polybag. Research was designed follow the Completely Randomized Design with 4 replications. The result of this study as follow: The mother seed trees of sandalwood influenced germination process and seedling growth especially on height and number leavesof seedlings. Seedling growth from each mother seed trees follow models of logistic growth with high value of coefficient determination about > 0,83, and be found also, close correlation between growth of seedling height with growth of seedling leaves was marked by high value of coefficient correlation about >0.85.Several mother seed trees was marked with capital letter E, D, C, A and G are better than F and B.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Santalum album L., mother seed trees, germination, seedling growth, Belu.